2005
DOI: 10.1002/chem.200400616
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Topological Aspects of the High‐Temperature Phases and Decomposition Products of the Alkali‐Metal Oxalates M2[C2O4] (M=K, Rb, Cs)

Abstract: The high-temperature phases of the alkali-metal oxalates M2[C2O4] (M = K, Rb, Cs), and their decomposition products M2[CO3] (M = K, Rb, Cs), were investigated by fast, angle-dispersive X-ray powder diffraction with an image-plate detector, and also by simultaneous differential thermal analysis (DTA)/thermogravimetric analysis (TGA)/mass spectrometry (MS) and differential scanning calorimetry (DSC) techniques. The following phases, in order of decreasing temperature, were observed and crystallographically chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 35 publications
9
42
0
Order By: Relevance
“…Presented results show that despite the different crystal structure than in case of lithium and sodium oxalates, the properties of electronic structure, electron density topology and the results of BVM analysis are very similar to those obtained for previous two cases, which allow us to assume the same pathway of thermal decomposition process of anhydrous potassium oxalate as earlier: first C-C bond breaks, which due to excessive thermal energy leads to breaking free of remaining COO -anions and next, as a result of their translational and rotational movements leads to the formation of unstable [OCOCO 2 ] 2-anions, which afterward decompose to CO 3 2-anions and carbon oxide(II) molecules [31][32][33]. The final step of this process consists of the structural alteration, which-due to very high similarity of anhydrous potassium oxalate and potassium carbonate structures-should undergo very easily, resulting in the formation of potassium carbonate as a final product of thermal decomposition process (topochemical reaction [26]).…”
Section: Anhydrous Lithium Oxalatementioning
confidence: 97%
See 1 more Smart Citation
“…Presented results show that despite the different crystal structure than in case of lithium and sodium oxalates, the properties of electronic structure, electron density topology and the results of BVM analysis are very similar to those obtained for previous two cases, which allow us to assume the same pathway of thermal decomposition process of anhydrous potassium oxalate as earlier: first C-C bond breaks, which due to excessive thermal energy leads to breaking free of remaining COO -anions and next, as a result of their translational and rotational movements leads to the formation of unstable [OCOCO 2 ] 2-anions, which afterward decompose to CO 3 2-anions and carbon oxide(II) molecules [31][32][33]. The final step of this process consists of the structural alteration, which-due to very high similarity of anhydrous potassium oxalate and potassium carbonate structures-should undergo very easily, resulting in the formation of potassium carbonate as a final product of thermal decomposition process (topochemical reaction [26]).…”
Section: Anhydrous Lithium Oxalatementioning
confidence: 97%
“…findings-a-Rb 2 C 2 O 4 decomposes thermally to rubidium carbonate and carbon oxide(II) [31,34,35]. Detailed analysis of the obtained results allows us to propose the following pathway of thermal decomposition process of anhydrous a-rubidium oxalate: first C-C bondthe weakest one in the structure-breaks, which is followed by breaking free of remaining COO -anions (breaking Rb-O bonds) and then due to their thermally activated translational and rotational movements leads to the formation of unstable [OCOCO 2 ] 2-anions, subsequently decomposed to CO 3 2-anions and carbon oxide(II) molecules.…”
Section: Anhydrous Lithium Oxalatementioning
confidence: 99%
“…However, such idealized configuration led to the formation of unrealistically short C-O bond distances of 1.19 Å [4]. Moreover, a recent article on the crystal structure of the high-temperature decomposition products of alkali-metal oxalates [17] indicated, from synchrotron powder diffraction data, that both -K 2 CO 3 and -Rb 2 CO 3 are isostructural with -Na 2 CO 3 but they show considerable disorder at the O site. At the !…”
Section: Introductionmentioning
confidence: 99%
“…Ballirano that, from Rietveld refinement of neutron powder diffraction data collected at 793 K, a very large anisotropy for the thermal motion in -Na 2 CO 3 has been reported [24], the largest vibrations being parallel to c. Such large thermal motion was also tentatively modelled by disordering the carbonate group. Moreover, a recent article on the crystal structure of the high-temperature decomposition products of alkali-metal oxalates [17] indicated, from synchrotron powder diffraction data, that both -K 2 CO 3 and -Rb 2 CO 3 are isostructural with -Na 2 CO 3 , but they show considerable disorder at the O site. Therefore, the oxygen atoms position was approximated by distributing them between two sites, the first, O(I), at x, Àx, 1/4 with x ca 0.8 and the second, O(II), at general position x, y, z with x ca 0.7, y and z ca 0.15.…”
mentioning
confidence: 99%
“…indicated that potassium was present as the form of oxalates and/or carbonates in raw bamboo and that most of them changed into the carbonates in the process of carbonization at 500 °C and 2 hours 24) .…”
Section: Surface and Pore Properties Of The Air Oxidation Bamboo Charmentioning
confidence: 99%